Wanita Karir dan Problem Pendidikan Anak - Yasin, A. Fatah (ULUL ALBAB Jurnal Studi Islam, 2001)
Interaction is perceived as an important need to create a harmonious family. Every person is equipped with the capability to interact with other but not many are able to have good interactions with others. People commonly think that a family with a career woman mother does not have sufficient good interactions. This paper shows, however, thatÂ  career women family can have more conducive environment to obtain a good interaction. It shows that the career woman Â mother is able to create intensive qualified interactions among the family members.